Functions and structure of code-switching: An analysis of the Egyptian novel mawlana - Hammoudeh, Ro'ya Mahmoud (AUC Knowledge Fountain, 2018)
This study aims to explore the social functions underlying the code-switch (CS) between MSA and ECA with a focus on the most salient linguistic structures characterizing the switch. Data were collected and analyzed from excerpts of Ibrahim Eissa's novel 'Mawlana'. Eighty-five instances of code-switching were detected to take place via speeches conveyed by the novel's main character, Sheikh Hatem. Findings relevant to the social functions of the code-switch were analyzed compared to Bassiouney's (2006) proposition on the subject. Alternatively, results following the linguistic structure of the code-switch were measured against Badawi's (1973) description of the colloquial of the educated level, aamiyyat l- mothaqqafiin. Results showed that the switch from MSA to ECA served the social functions of sarcasm, joking and clarification, whereas the switch to MSA was found to satisfy the speaker's intent to quote Quranic verses or prophetic narrations. The switch to ECA was observed to take place at the lexical, phrasal and sentential level, while the switch to MSA seemed to only occur at the lexical and sentential level. Furthermore, the use of lexical items or demonstrative particles was evident on the lexical level, with idiomatic expressions and negations marking the switch on the phrasal level. Alternatively, negative, interrogative, relative and accusative particles signaled the switch on the sentence level. This study stresses on the importance of integrating MSA and ECA in Arabic as a foreign language (AFL) classes in order to build speakers' capacities to communicate using the educated spoken Arabic.